Making Violence Transparent: Ranking Police Departments in Major U.S. Cities to Make Black Lives Matter. (4th March 2021) - Bearfield, Domonic; Maranto, Robert; Wolf, Patrick J.
Abstract : This study suggests that police professionalism can both reduce homicides and prevent unnecessary police-related civilian deaths (PRCD). Those improvements would particularly benefit African Americans, who fall victim to both at disproportionately high rates. Policing practices regarding African Americans have a frustrating history, highlighted by the fact that PRCD generally, and for African Americans in particular, were not even counted until recently. Since what is counted shapes the behaviors of street-level bureaucrats, this article employs a performance algorithm, the Police Performance Index, using homicide, PRCD, and poverty rates to rank police departments in 23 of America's 25 largest cities, those for which data are currently available. We argue that successful policing entails respecting all citizens (minimizing PRCD) while maintaining safe communities (minimizing homicides). Doing so is more difficult in high poverty communities. Our findings that certain cities achieve better policing outcomes suggest that reforms enhancing police professionalism would do more to make Black (and non-Black) lives matter.